Person Re-Identification 2014
DOI: 10.1007/978-1-4471-6296-4_10
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Feature Importance for Re-identification

Abstract: Person re-identification methods seek robust person matching through combining feature types. Often, these features are assigned implicitly with a single vector of global weights, which are assumed to be universally and equally good for matching all individuals, independent of their different appearances. In this study, we present a comprehensive comparison and evaluation of up-to-date imagery features for person re-identification. We show that certain features play more important roles than others for differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 40 publications
(113 reference statements)
0
16
0
Order By: Relevance
“…Feature selection has been used to improve the discriminative power of the distance function by evaluating the discriminative importance of different types of features to properly weight them, as it is presented in [214].…”
Section: A) Feature Selection Methodsmentioning
confidence: 99%
“…Feature selection has been used to improve the discriminative power of the distance function by evaluating the discriminative importance of different types of features to properly weight them, as it is presented in [214].…”
Section: A) Feature Selection Methodsmentioning
confidence: 99%
“…This task is a typical person re-identification problem where a specific person is queried in a database of known identities. Several studies [41,42] have shown that HSV and YCbCr features exhibit superior person re-identification performances over other features, i.e., these features are highly sensitive to the unique visual appearance of each person. Thus, the log-likelihood appearance value for each detection bolddt is computed by comparing the normalized 48 bin HSV color histogram to the HSV histogram of the target.…”
Section: Motion and Observation Modelsmentioning
confidence: 99%
“…These mentioned methods address the learning of a global weighting that reflects the stability of each feature component across two cameras, so they can be grouped under the paradigm of Global Feature Importance (GFI) methods. On contrary, in [33], a Prototype-Sensitive Feature Importance based method is proposed to adaptively weight features according to different clusters of population.…”
Section: Related Workmentioning
confidence: 99%
“…In [33], a Prototype-Sensitive Feature Importance based method is proposed to adaptively weight features according to different clusters of population. On contrary, [36] present a Global Feature Importance (GFI) approach, addressing the learning of a global weighting, i.e.…”
Section: Fine-tuned Model Evaluationmentioning
confidence: 99%